PENINGKATAN EFISIENSI MANUFAKTUR RING INJECT CAVITY MOULD DENGAN PENGGUNAAN FIXTURE PADA MESIN CNC MILLING DI PT. BIL - Hartman, Bemly; Izzat, Albait Malikul; Nursalam, Rachmat; Heryana, Ghany (Jurnal Ilmiah Teknologi dan Rekayasa, 2024)
Ring inject cavity mould is a crucial component in the injection stretch blow process used in plastic bottle manufacturing machines. This process involves five main steps: injection, conditioning, stretching, blowing, and ejecting. However, damage to the ring inject cavity mould is a common occurrence, necessitating periodic component replacement. The objective of this research is to identify a more efficient production method for manufacturing ring inject cavity moulds at PT BIL. Currently, the manufacturing process is carried out using a conventional lathe, which requires 64 hours to produce 16 pieces in a single work order. This research aims to evaluate the effectiveness of using a CNC (Computer Numerical Control) milling machine as a more efficient alternative. The methodology employed involves comparing the production time between the conventional lathe and CNC milling, as well as implementing a fixture as an auxiliary tool in the CNC milling process. The data collected includes production time and product quality. The research results indicate that the use of CNC Milling significantly reduces production time to only 24 hours for 16 rings in a single work order, compared to the 64 hours required by the conventional lathe. Additionally, the quality of the products produced also meets the expected standards. The conclusion of this research is that the transition from a conventional lathe to CNC milling with the use of a fixture can improve the production efficiency of ring inject cavity moulds at PT BIL, with faster production time and maintained quality.